Intervention among new parents followed up by an interview study exploring their experiences of telemedicine after early postnatal discharge. Issue 6 (June 2015) - Danbjørg, D.B.; Wagner, L.; Kristensen, B.R.; Clemensen, J.
Abstract Background a move towards earlier postnatal discharge raises the challenge of finding new ways to support families when they are discharged early after childbirth. Aim to explore how postnatal parents experienced the use of telemedicine following early discharge from hospital (i.e. 24 hours after childbirth) by investigating if they consider that their postnatal needs are met, and whether or not they experience a sense of security and parental self-efficacy. Design intervention followed by a qualitative interview study. The intervention took place on a postnatal ward with approximately 1000 births a year. An app including chat, a knowledgebase and automated messages was trialled between postnatal parents at home and the hospital. Parents had access to the app for seven days after discharge. Population 42 new mothers were recruited from the postnatal ward in accordance with the inclusion criteria (i.e. discharged within 24 hours of childbirth). Both parents were invited for interview. Methods 42 sets of parents participated in the trial, and 28 sets agreed to be interviewed. Interviews (n=28) were conducted with 27 mothers and 11 fathers. Parents were interviewed together in 10 cases, 17 mothers were interviewed alone, and one father was interviewed alone. The data analysis was inspired by systematic text condensation based on Giorgi׳s descriptive phenomenological method. Findings parents were confident in use of the app, and did not experience any barriers in contacting the nurses via asynchronous communication. Parents received timely information and guidance by communicating online, and felt that their follow-up support needs were met. Conclusions parents viewed the app as a lifeline, and saw it as a means of informing and guiding them following early discharge from hospital after childbirth. As such, this app shows potential for enhancing self-efficacy and postnatal sense of security.